Training on Structural Equation Modelling (SEM) Analysis for Lecturers at Patompo University: Pelatihan Analisis Structural Equation Modelling (SEM) Bagi Dosen Universitas Patompo - Meliyana, Sitti Masyitah; Ruliana, Ruliana; Sudarmin, Sudarmin; Rais, Zulkifli (Mattawang: Jurnal Pengabdian Masyarakat, 2025)
This community service project aims to enhance the understanding and skills of lecturers at Universitas Patompo in using Structural Equation Modelling (SEM) for research data analysis. The activity took place on September 18, 2024, and was attended by 28 lecturers. The main issues faced by the participants were a lack of understanding of SEM techniques and limited skills in using statistical software for analysis. The solution offered was an intensive training session that included the introduction of statistical software and the application of SEM using the Jamovi software. In addition, a community action planning process was implemented, involving the lecturers in the organization of the training. The results of this project showed a significant improvement in the participants' understanding and skills in SEM analysis.